Security [videorecording (DVD)] - Sullivan, John, 1978-; Mosher, Tony; Banderas, Antonio; Kingsley, Ben, 1943-; McIntyre, Liam, 1982-; Le, Cung, 1972-; Rocha, Katherine Mary de la; Lindberg, Chad; Wang, Dongcheng, 1981-; Wright, Gabriella, 1982- (Universal Pictures Home Entertainment, 2017)
Eddie Deacon is a war hero suffering from post-traumatic stress disorder who takes a low-key job as a nighttime security guard at a shopping mall to get back on his feet. Things are uneventful until a gang of brutal ruthless bikers and their psychotic leader chase an innocent girl into the mall in an attempt to kill her and keep her from testifying against them. Now Eddie and his team of unarmed guards are her only hope for survival.